2014
DOI: 10.1007/s10548-014-0407-1
|View full text |Cite
|
Sign up to set email alerts
|

Are Epilepsy-Related fMRI Components Dependent on the Presence of Interictal Epileptic Discharges in Scalp EEG?

Abstract: Spatial independent component analysis (ICA) is increasingly being used to extract resting-state networks from fMRI data. Previous studies showed that ICA also reveals independent components (ICs) related to the seizure onset zone. However, it is currently unknown how these epileptic ICs depend on the presence of interictal epileptic discharges (IEDs) in the EEG. The goal of this study was to explore the relation between ICs obtained from fMRI epochs during the occurrence of IEDs in the EEG and those without I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 45 publications
5
17
0
Order By: Relevance
“…On the other hand, based on our experience, even in cases where EEG-fMRI shows multiple areas of BOLD activation, these activation clusters are represented in different independent components, representing different aspects of epileptic activity [21]. Similar findings were reported in a recent study (van Houdt et al, 2014). The authors argued that in patients where the EEG-fMRI patterns included more than one activation cluster, one of them reflected the onset area, while others were related to propagation.…”
Section: Discussionsupporting
confidence: 75%
“…On the other hand, based on our experience, even in cases where EEG-fMRI shows multiple areas of BOLD activation, these activation clusters are represented in different independent components, representing different aspects of epileptic activity [21]. Similar findings were reported in a recent study (van Houdt et al, 2014). The authors argued that in patients where the EEG-fMRI patterns included more than one activation cluster, one of them reflected the onset area, while others were related to propagation.…”
Section: Discussionsupporting
confidence: 75%
“…Our findings are concordant with those of other recent studies investigating connectivity patterns in the absence of scalp IEDs: a seed‐based FC study in patients with frontal lobe epilepsy revealed that the FC features of the epileptic network were similar when comparing fMRI dataset with visible IEDs in the simultaneous scalp EEG to dataset without IEDs. Another study, using ICA on resting‐state fMRI in patients with drug‐resistant epilepsy, showed that the BOLD components related to the epileptogenic region of a patient are similar in EEG‐fMRI data with and without visible concomitant scalp IEDs . Uniquely, our study included the whole BOLD dataset from which we regressed out the effect of the IEDs in order to avoid any confounding effect that could occur between consecutive recording sessions.…”
Section: Discussionmentioning
confidence: 99%
“…One possibility is that networks involved in the expression of scalp epileptic activity show fMRI connectivity that is observable when discharges are absent, akin to the intrinsic correlations observed in physiologic networks in the absence of task performance 11 -that is, epileptic activity may represent the "tip of the iceberg" against a background of ongoing atypical network interactions. 30 Alternatively, it is possible that small sample size, electrical events not visible on scalp EEG, or fMRI signal changes preceding the onset of visible epileptic activity, 31 may have impeded detection of differences between fMRI periods with and without discharges. However, our results are consistent with previous EEG-fMRI studies in genetic generalized epilepsy 32 and localization-related epilepsy, 30 where persisting fMRI connectivity abnormalities were observed in the absence of scalp-recorded discharges.…”
Section: Does Epileptic Activity Disrupt Network Interactions?mentioning
confidence: 99%
“…30 Alternatively, it is possible that small sample size, electrical events not visible on scalp EEG, or fMRI signal changes preceding the onset of visible epileptic activity, 31 may have impeded detection of differences between fMRI periods with and without discharges. However, our results are consistent with previous EEG-fMRI studies in genetic generalized epilepsy 32 and localization-related epilepsy, 30 where persisting fMRI connectivity abnormalities were observed in the absence of scalp-recorded discharges.…”
Section: Does Epileptic Activity Disrupt Network Interactions?mentioning
confidence: 99%